2019
DOI: 10.1038/s41598-019-52400-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR interference to interrogate genes that control biofilm formation in Pseudomonas fluorescens

Abstract: Bacterial biofilm formation involves signaling and regulatory pathways that control the transition from motile to sessile lifestyle, production of extracellular polymeric matrix, and maturation of the biofilm 3D structure. Biofilms are extensively studied because of their importance in biomedical, ecological and industrial settings. Gene inactivation is a powerful approach for functional studies but it is often labor intensive, limiting systematic gene surveys to the most tractable bacterial hosts. Here, we ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 89 publications
(108 reference statements)
1
25
0
Order By: Relevance
“…Previously, CRISPRi of quorum sensing gene luxS was used to inhibit biofilm formation in E. coli (Zuberi et al 2017). Later, biofilm formation and swarming motility were strongly inhibited by CRISPRi of environmental sensor histidine kinase gene gacS in Pseudomonas fluorescens (Noirot-Gros et al 2019). In B. subtilis, mutations in spo0A caused a defect in biofilm formation (Hamon and Lazazzera 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, CRISPRi of quorum sensing gene luxS was used to inhibit biofilm formation in E. coli (Zuberi et al 2017). Later, biofilm formation and swarming motility were strongly inhibited by CRISPRi of environmental sensor histidine kinase gene gacS in Pseudomonas fluorescens (Noirot-Gros et al 2019). In B. subtilis, mutations in spo0A caused a defect in biofilm formation (Hamon and Lazazzera 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Another novel approach that can be harnessed to tackle the biofilm-related issues is the use of a clustered, regularly interspaced short palindromic repeats (CRISPR)-mediated method. Studies have revealed the potential use of the CRISPR interference (CRISPRi) system as a strategy to inhibit bacterial biofilm [ 242 , 243 ]. Using the CRISPRi method, Zuberi et al demonstrated that inhibition of genes that are directly involved in quorum sensing could lead to the inhibition of biofilm formation in E. coli [ 242 ].…”
Section: Other Potential Approaches In the Treatment And/or Prevenmentioning
confidence: 99%
“…Using the CRISPRi method, Zuberi et al demonstrated that inhibition of genes that are directly involved in quorum sensing could lead to the inhibition of biofilm formation in E. coli [ 242 ]. Taking a similar step using P. fluorescens as a model, Noirot-Gros et al (2019) investigated the gene network that leads to the disruption in the biofilm formation [ 243 ]. It seems that the silencing of bacterial genes responsible in the formation of biofilm by CRISPRi may hold a strategic advantage in the management of biofilm-associated polymicrobial diseases.…”
Section: Other Potential Approaches In the Treatment And/or Prevenmentioning
confidence: 99%
“…Both systems were demonstrated to be functional for repression of genes encoding fluorescent proteins, and Kim et al (2020) also employed CRISPRi for metabolic engineering via gene repression by depleting the GlpR regulator to enhance the glycerol-dependent synthesis of mevalonate. Other examples on the development of CRISPRi systems have been reported for P. aeruginosa (Peters et al, 2019;Qu et al, 2019) and P. fluorescens (Noirot-Gros et al, 2019). While the CRISPRi toolbox for Pseudomonas species offers alternatives depending on the intended application (ranging from fundamental studies to simple metabolic engineering manipulations), the techniques applied so far are afflicted by either leaky expression of the components or limited ability to titrate repression levelsthus restricting the applicability of the tool in complex engineering approaches.…”
Section: Introductionmentioning
confidence: 99%
“…aeruginosa (Peters et al , ; Qu et al , ) and P . fluorescens (Noirot‐Gros et al , ). While the CRISPRi toolbox for Pseudomonas species offers alternatives depending on the intended application (ranging from fundamental studies to simple metabolic engineering manipulations), the techniques applied so far are afflicted by either leaky expression of the components or limited ability to titrate repression levels – thus restricting the applicability of the tool in complex engineering approaches.…”
Section: Introductionmentioning
confidence: 99%